EPISTEMOLOGI PAJAK, PERSPEKTIF HUKUM TATA NEGARA TAXES EPISTEMOLOGY, CONSTITUTIONAL LAW PERSPECTIVE - Thohari, A. Ahsin (Jurnal Legislasi Indonesia, 2011)
Span of the history of taxation in this world extend from the time of the pyramids inEgypt (3000 BC-2800 BC), Persian (500 BC), Babylon (612 BC-539 BC), Roman (27BC-476 BC), India (500 BC-550 BC), Arabic (11th century), until the time of socialnetworking wibesites are created in this information age with all aspects of thedynamics, sophistication, and the adjustments to the surrounding context. However,the history of taxation finds political momentum, and then into the world of discourse,during British colonial rule arbitrarily impose taxes in the country towns, namely theUnited States. “No taxation without representation”, according to the ever popularslogan in the 13 (thirteen) British colony in 1750-1760 which is one of the maincauses of the American Revolution to resist the reign of King George III. The lack ofdirect representation for the colonists in the distant British Parliament is consideredas an illegal act and part of the act of denial of their rights as part of the rights ofEnglishmen), so the colonial government was not authorized to collect taxes frompeople in the all form. The slogan created by Jonathan Mayhew was sharpened byJames Otis with a more provocative phrase, “Taxation without representation is tyranny”.In short, tax collection by the government without determined by representativeinstitutions is a form of oppressive power. In Indonesian context, the tax is thecrystallization of people’s contributions to the state treasury under the laws enforced,with no direct remuneration. Tax authorities levied based on legal norms to cover thecost of production of goods and services collectively to achieve common prosperity.However, with so many tax chaos today, this kind of tax epistemology seemed distant.